Pendampingan dan Pelatihan Pembuatan Media Pembelajaran Augmented Reality bagi Guru Sekolah Luar Biasa Kabupaten Dharmasraya Untuk Meningkatkan Kompetensi Guru - Ambiyar, Ambiyar; Efendi, Raimon; Waskito, Waskito; Indra, Indra; Yanti, Arifatul; Agustin Wulandari, Ratih (Journal Of Human And Education (JAHE), 2024)
This Community Service activity focuses on mentoring and training in the creation of learning media using Augmented Reality (AR) technology for teachers of Special Schools (SLB) in Dharmasraya Regency. The aim of this activity is to enhance teachers' competencies in applying the latest educational technology to enrich their teaching methods. The method used is Service-Learning, which includes theoretical and practical training, socialization of AR technology, and continuous evaluation through surveys and feedback from participants. The results of the activity show a significant increase in teachers' understanding and ability to use AR in the learning process, as evidenced by improvements in pre-test and post-test scores as well as positive feedback from the teachers. The implications of this activity indicate that the implementation of AR in learning at SLB can enhance interactivity and effectiveness in teaching, as well as motivate students with special needs through more inclusive and engaging methods. Recommendations for the future include further development of the AR training curriculum and the provision of ongoing technical support for teachers at SLB.